2023
DOI: 10.1007/s11357-023-00791-9
|View full text |Cite|
|
Sign up to set email alerts
|

Capturing postural blood pressure dynamics with near-infrared spectroscopy-measured cerebral oxygenation

Abstract: Orthostatic hypotension (OH) is highly prevalent in older adults and associated with dizziness, falls, lower physical and cognitive function, cardiovascular disease, and mortality. OH is currently diagnosed in a clinical setting with single-time point cuff measurements. Continuous blood pressure (BP) devices can measure OH dynamics but cannot be used for daily life monitoring. Near-infrared spectroscopy (NIRS) has potential diagnostic value in measuring cerebral oxygenation continuously over a longer time peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
2
1
0
Order By: Relevance
“…This corresponds to the expected effect of cerebral autoregulation attenuating the impact of a BP drop on CBF [42], which would result in larger drops in skin perfusion than in brain perfusion. Lower oxygenation recovery values are as expected because OH is defined as impaired BP recovery, and BP and oxygenation are correlated [21]. Within the OH group, we observed large differences in oxygenation response, but OH severity in terms of BP recovery also differed.…”
Section: Face Validitysupporting
confidence: 78%
See 2 more Smart Citations
“…This corresponds to the expected effect of cerebral autoregulation attenuating the impact of a BP drop on CBF [42], which would result in larger drops in skin perfusion than in brain perfusion. Lower oxygenation recovery values are as expected because OH is defined as impaired BP recovery, and BP and oxygenation are correlated [21]. Within the OH group, we observed large differences in oxygenation response, but OH severity in terms of BP recovery also differed.…”
Section: Face Validitysupporting
confidence: 78%
“…Cerebral oxygenation responses to standardized supine-stand tests at home followed a similar course as tests performed in the laboratory in mostly healthy younger and older adults [21,41]. This study revealed lower oxygenation recovery values for older adults with OH.…”
Section: Face Validitysupporting
confidence: 60%
See 1 more Smart Citation